Peluang dan Tantangan Pemberlakuan Undang-Undang No. 23 Pasal 22 Tahun 2011 Tentang Zakat Sebagai Pengurang Pajak Penghasilan - Maulida, Minati; Ulfah, Aulia (Fakultas Syariah dan Ekonomi Islam Institut Pesantren Mathali'ul Falah, 2023)
The obligation to pay zakat and the obligation to pay taxes for Muslims causes double charges or double burdens so that it will make it difficult for property owners and cause counterproductive effects. As a solution so that zakat must not be exposed to a double burden, the government issued a regulation, namely Law Number 23 of 2011 article 22 concerning zakat as a deduction from income tax. The purpose of this study is as one of the socialization efforts to muzakki on zakat as an income tax deduction and provide a positive perception of zakat and tax management. The methods used are qualitative approaches with the type of field research (field research) and data analysis using qualitative descriptive methods. From the results of research and analysis on zakat regulations as income tax deductions cannot be implemented, because there is no cooperation between BAZNAS and Primary Tax even though there is clearly a law regulating it. The lack of socialization carried out by BAZNAS makes the muzakki unaware of the law on zakat as an income tax deduction and there are still many muzakki handing over their zakat directly to those who are entitled to receive it because the reach is easier.